Time-Frequency Analysis of Brain Electrical Activity – Adaptive Approximations - Blinowska, K. J.; Durka, P. J.; ygierewicz, J. Z (Methods of Information in Medicine, 2004)
Objectives: We present an approach to time-frequency analysis of bioelectrical signals.Methods: The method relays on the decomposition of the signal into a set of waveforms that have good localization both in time and in frequency. The waveforms belong to a highly redundant set of functions – allowing for a very accurate description of signal components.Results: Properties of the method are illustrated by simulations and applications to EEG.Conclusion: The presented method delivers a common formalism suitable for describing both gross statistical properties of structures present in bioelectrical signals, as well as microstructure of chosen phenomena.
Keywords: Time-frequency representations; adaptive approximations; matching pursuit; non-stationary signals; EEG; LFP